-5(2t-3)+8t=7t-2

Simple and best practice solution for -5(2t-3)+8t=7t-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5(2t-3)+8t=7t-2 equation:



-5(2t-3)+8t=7t-2
We move all terms to the left:
-5(2t-3)+8t-(7t-2)=0
We add all the numbers together, and all the variables
8t-5(2t-3)-(7t-2)=0
We multiply parentheses
8t-10t-(7t-2)+15=0
We get rid of parentheses
8t-10t-7t+2+15=0
We add all the numbers together, and all the variables
-9t+17=0
We move all terms containing t to the left, all other terms to the right
-9t=-17
t=-17/-9
t=1+8/9

See similar equations:

| 102=8x=6 | | 10m=7-m | | 10=z–6 | | x/10=121/11 | | -3(v+1)=12 | | 5(x+1)=3(3x+2)-4 | | -28=8-9w | | -5(8p+6)=5-5 | | 2(-x+4)+5x-3=2(−x+4) | | 54-5u=4u | | 9x+4=3x+10x | | 9x+4=3x+10xx= | | 9x+4=3x+10x= | | x−4+1−7x=−8x+4+2x−7 | | 6d=2(d-4 | | 6d=2(d-2) | | 3x8+4=2x-8+x | | 2(2x+9)-2(×+3)=×+11-5(4-x) | | 7(-3-6x)+3x=10-8x | | 3x-15/4=21 | | 84=7(-x+4) | | 68/17=56/x-5 | | 45×q=1 | | -4(5+3x)=8(4-8x) | | 1/3b+1=5/6 | | 5x​+2x​=7 | | -14-5x=10 | | 21=-8=n | | 7×3a(3a+5a)=2 | | 22-7k=-6(6k+6) | | 5x+2=2x1 | | 12x-24=3+2x |

Equations solver categories